Taxonomy of southern California Erebidae and Noctuidae (Lepidoptera) with descriptions of twenty one new species - Mustelin, Tomas (Zootaxa, 2006)
Twenty-two new taxa of owlet moths (families Erebidae and Noctuidae) are described along with three status changes from subspecies to species, eleven new synonymies, and twenty-one new combinations. Of the new taxa, one is a new tribe, Annaphilini Mustelin, n. tribe, and twenty-one are new species from southern California: Drasteria convergens Mustelin, n.sp., Tarachidia nigra Mustelin, n.sp., Oncocnemis duplex Troubridge and Mustelin, n.sp., O. helena Mustelin, n.sp., O. sala Mustelin, n.sp., O. kelsoensis Robertson and Mustelin, n.sp., Annaphila scurlockorum Sala and Mustelin, n.sp., Cryphia flavipuncta Mustelin, n.sp., Protoperigea umbricata Mustelin, n.sp., P. subterminata Mustelin, n.sp., P. parvulata Mustelin, n.sp., P. calientensis Mustelin, n.sp., Aseptis fanatica Mustelin, n.sp., Aseptis torreyana Mustelin, n.sp., Apamea robertsoni Mikkola and Mustelin, n.sp., A. digitula Mustelin and Mikkola, n.sp., Photedes sofiae Mustelin, n.sp., Mammifrontia sarae Mustelin, n.sp., Lasionycta sala Troubridge and Mustelin, n.sp., Trichocerapoda harbisoni Mustelin, n.sp., and T. oceanis Robertson and Mustelin, n.sp. The relationship of these new species to their closest relatives is discussed. The following new combinations are proposed to maintain consistency in generic concepts between the European and North American faunas: Agrochola decipiens (Grote, 1881), n. comb., Anarta chartaria (Grote, 1873), n. comb., Anarta trifolii (Hufnagel, 1766), n. comb., Anarta mutata (Dod, 1913), n. comb., Anarta fulgora (Barnes & McDunnough, 1918), n. comb., Anarta castrae (Barnes & McDunnough, 1912), n. comb., Anarta hamata (McDunnough, 1930), n. comb., Anarta oregonica (Grote, 1881), n. comb., Anarta montanica (McDunnough, 1930), n. comb., Anarta columbica (McDunnough, 1930), n. comb., Anarta alta (Barnes & Benjamin, 1924), n. comb., Anarta subalbida (Barnes & Benjamin, 1924), n. comb., Anarta obesula (Smith, 1904), n. comb., Anarta farnhami (Grote, 1873), n. comb., Anarta crotchi (Grote, 1880), n. comb., Anarta oaklandiae (McDunnough, 1937), n. comb., Anarta projecta (McDunnough, 1938), n. comb., Anarta edwardsii (Smith, 1888), n. comb., Anarta florida (Smith, 1900), n. comb., Anarta antica (Smith, 1891), n. comb., and Anarta decepta (Grote, 1883), n. comb.